El infanticidio consumado por circunstancias de inestabilidad socio – económica, necesidad de tipificar como figura delictiva que garantice la vida dentro del código penal ecuatoriano - Peña Moya, Jaqueline Elizabeth (2014)
Criminal Law and Legal different figures, saying the current trends of criminal sciences , are the source of the aspects or principles of criminal law, which are essential in the legal structure - legal state, as the structure present criminal process scholars in the field, the importance and significance of the legal issue raised on the infanticide by socioeconomic instability, is set by the need to add guidance on the legal reasoning in regard to social prejudice and general commotion caused by this reprehensible illegal, to establish the right strategy to eradicate this way of producing the crime, which in the main, the study to verify the adequacy of legal rules to punish this mobile and the crime was necessary, in national legislation, by adapting penalties of this modus operandi. The theoretical content and empirical research on the development of legal research, contains the factual circumstances that helped to determine the precise contribution of the verification of the proposed objectives and the merits of the proposal, with the support of literary literature that they helped to the changes made as a major source of serious and proper study. This scientific research work, presenting it as a budget that comes from intellectual effort, where guidelines and scientific methodology, which interprets the whole investigation on the formula to adjust the Criminal Code, a provision that sanctions appear the infanticide, in the form of social economic situation, to minimize this mode of criminal involvement in the persons of the direct perpetrators.